Perancangan Sistem Informasi Peminjaman Barang Berbasis Web Pada Kantor Hu Kabar Priangan - Susanto, Julius Wijaya; Utami, Lita Lestari (Jurnal Tika, 2024)
HU Kabar Priangan is a company engaged in the media sector that has a great responsibility in presenting information both in the form of newspapers and online articles and advertising services. This company has related problems in borrowing goods still using a semi-manual system using spreadsheets for managing goods, borrowing, and returning goods. Semi-manual recording using spreadsheets in a company has obstacles and weaknesses including can result in data errors, no history, and can lose information. The system that is run has not fully helped the work, because the need for effective and efficient data and can be needed (availability) has not been met. With these problems, this research will be designed and built a web-based goods lending information system that functions to facilitate the management of goods data. With the goods lending information system, the process of borrowing, returning, monitoring goods, and searching for the status of goods can be easily and quickly carried out. The system development method used in this study uses the Waterfall method, and for system design uses UML (Unified Modeling Language). The final result of this research is a web-based goods lending information system using the Laravel 9 framework and MySQL as a database that can facilitate the process of managing goods lending